Factors contributing to stress in teenagers - Nazario, Valerie T.
This study determined the different stressors affecting the teenagers of today regarding academic and personal issues, family matters, environmental demands and interpersonal relationships. The respondents of the study were eighty (80) teenagers age 13-19 years old from Kingsville Subdivision, Antipolo City.Threspondents were conveniently selected with the assistance of the chairman of Kingsville Subdivision. The responses of the teenagers regarding the stressors were determined by utilizing a survey questionnaire. The questionnaire for this study consisted of five (5) general areas of stress namely, Academic Issues, Personal Concerns, Family Matters, Environmental Demands and Interpersonal Stressors. The responses of the respondents were based on rank preference from one to five (1-5) with rank one (1) as the most stressful and rank five (5) as the least stressful. Mean-rank and standard deviation was used to analyze the data. Findings revealed that the teen-agers perceived the stressors that affected them most under Academic Issues, Personal Concerns, Family Matters, Environmental Demands and Interpersonal Stressors were failing in school requirements, physical appearance, parents' high expectation from their children, death of someone close and having misunderstanding with peers respectively.